A polygraph on the small screen: the Millor Fernandes' television humor (1959-1965) - Busetto, Aureo [UNESP] (Univ Federal Uberlandia, 2016)
This article is guided by the goal of knowing and analyzing the polygraph Millor Fernandes' television experiences, which were designed to show on TV, in its early stages in Brazil, a kind of humor that was critical, reflective, and innovative compared to regular humoristic TV shows. Combining narrative and cartoons, Millor transitions among entertainment, information, and knowledge. The historical approach of the author's humoristic text, co-text, and context also provide elements that shed light on the main relations between early TV, press, and national politics, both in democracy and under military dictatorship.
Keywords: Millor Fernandes, humor; television